Biomimetic hydrogels based on natural dextran and gelatin for vascular tissue engineering application - Liu, YunXiao (2010)
Hydrogels are crosslinked polymer networks with high water content. They have the capability to mimic native ECM and thus are highly desirable as 3D scaffolds for cell encapsulation. Synthetic hydrogels for cell encapsulation have hitherto been based on poly(ethylene glycol), which is non-natural, non-biodegradable, and only terminal-functionalizable. Dextran is highly hydrophilic but also biodegradable and pendant-functionalizable. More importantly, it resembles the native glycosaminoglycans.